Стан і перспективи систем керування енергозаощадженням у металургії - Труфанов, І.; Метельський, В.; Андріяс, І.; Богданова, Л. (Видавництво Національного університету “Львівська політехніка”, 2005)
The analysis of a modern state and substantiation of new efficient technologies of energy saving, energy supply and technology equipment efficiency improvement in metallurgy of ferrous metals and electrometallurgy precision alloys black and heavy black and nonferrous metals will be carried out.
Keywords: 621.365.3.036.7; 621.07.014